Ancient Aztecs - Oachs, Emily Rose (Ancient civilizations (Bellwether Media), 2020)
Explores the history of the ancient Aztec civilization, discussing the Aztecs' rulers, daily life, and culture. Also describes the fall of the Aztec empire. Includes a timeline, critical thinking questions, color photographs, a glossary, and further resources.